(untitled) ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2023)
This scientific article delves into the interconnectedness of language and culture by exploring the subfields of Contrastive Linguistics (CL) and Cultural Linguistics (CL). Together, these disciplines shed light on the correlation between language, society, and cultural values. While Contrastive Linguistics focuses on the examination of linguistic differences between languages, Cultural Linguistics expands this analysis by investigating the cultural dimensions and implications of language use. This article emphasizes the significance of incorporating cultural perspectives into contrastive linguistic studies and presents how Cultural Linguistics adds depth to our understanding of language variation and cultural diversity.